2022
DOI: 10.1186/s40779-022-00430-y
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on the monitoring and treatment of sepsis-induced immunosuppression

Abstract: Emerged evidence has indicated that immunosuppression is involved in the occurrence and development of sepsis. To provide clinical practice recommendations on the immune function in sepsis, an expert consensus focusing on the monitoring and treatment of sepsis-induced immunosuppression was developed. Literature related to the immune monitoring and treatment of sepsis were retrieved from PubMed, Web of Science, and Chinese National Knowledge Infrastructure to design items and expert opinions were collected thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 129 publications
0
17
0
Order By: Relevance
“…Immune cell surface markers, containing HLA‐DR, CD64, and PD‐1, are promising biomarkers for sepsis diagnosis and prognosis 19 . mHLA‐DR has been confirmed to be a reliable indicator for estimating sepsis‐induced immunesuppression 20,21 . The percentage of mHLA‐DR+ significantly decreased during sepsis, and the dynamic change in mHLA‐DR+ over time may be a reliable predictor for sepsis mortality 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell surface markers, containing HLA‐DR, CD64, and PD‐1, are promising biomarkers for sepsis diagnosis and prognosis 19 . mHLA‐DR has been confirmed to be a reliable indicator for estimating sepsis‐induced immunesuppression 20,21 . The percentage of mHLA‐DR+ significantly decreased during sepsis, and the dynamic change in mHLA‐DR+ over time may be a reliable predictor for sepsis mortality 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis and sepsis-related mortality increased significantly with age [32][33][34]. Old age (≥65 years old) is one of the high-risk factors for immunosuppression in septic patients [35]. Based on this, a subgroup analysis was conducted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is a complex disease. Although its etiology has been most recently defined as “a dysregulated host response to infection” [ 1 ], different patients may have prior exposure to different pathological processes, such as trauma, burns, or acute abdomen [ 2 ]. Also, the pathogens that cause such infections may vary, such as bacteria, viruses, or fungi [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression is an important cause of late death in early survivors of sepsis and remains difficult to treat [ 9 , 10 ]. Many studies have shown that lymphocyte failure contributes to immunosuppression in sepsis [ 2 , 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%